Exploring the socio-economic impacts of South Africa’s just energy transition (JET): a case study of coal-dependent communities in Mpumalanga - Ramparsad, Sherin (University of Pretoria, 2026)
Mini Dissertation (MBA)--University of Pretoria, 2025.